2022
DOI: 10.1111/nph.18040
|View full text |Cite
|
Sign up to set email alerts
|

SnRK2 subfamily I protein kinases regulate ethylene biosynthesis by phosphorylating HB transcription factors to induce ACO1 expression in apple

Abstract: Ethylene (ETH) controls climacteric fruit ripening and can be triggered by osmotic stress. However, the mechanism regulating ETH biosynthesis during fruit ripening and under osmotic stress is largely unknown in apple (Malus domestica).Here, we explored the roles of SnRK2 protein kinases in ETH biosynthesis related to fruit ripening and osmoregulation. We identified the substrates of MdSnRK2-I using phosphorylation analysis techniques. Finally, we identified the MdSnRK2-I-mediated signaling pathway for ETH bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 73 publications
(155 reference statements)
0
15
0
Order By: Relevance
“…However, the result was different with Lee et al (2007) and Meng et al (2020). This may be caused by the short expression time of VaAPL1 in tobacco mesophyll cells observed in this study (Jia et al, 2022;Ma et al, 2022) ), hydrogen peroxide (H 2 O 2 ), and hydroxyl radical (OH − ; Rodrigo-Moreno et al, 2013). High accumulation of ROS destroys redox homeostasis, leads to cell death, and reduces biomass (Czarnocka and Karpiński, 2018).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, the result was different with Lee et al (2007) and Meng et al (2020). This may be caused by the short expression time of VaAPL1 in tobacco mesophyll cells observed in this study (Jia et al, 2022;Ma et al, 2022) ), hydrogen peroxide (H 2 O 2 ), and hydroxyl radical (OH − ; Rodrigo-Moreno et al, 2013). High accumulation of ROS destroys redox homeostasis, leads to cell death, and reduces biomass (Czarnocka and Karpiński, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…However, the result was different with Lee et al (2007) and Meng et al (2020) . This may be caused by the short expression time of VaAPL1 in tobacco mesophyll cells observed in this study ( Jia et al, 2022 ; Ma et al, 2022 ). Our results indicated that overexpression of VaAPL1 resulted in a decrease in REC in VaAPL1 -overexpressing A. thaliana plants and OEs after LT stress ( Figures 2F , 5B ).…”
Section: Discussionmentioning
confidence: 83%
“…The lines with the highest CmNAC‐NOR expression ( CmNAC‐NOR S,N / cr‐nor #2 and #16, CmNAC‐NOR A,S / cr‐nor #9 and #13) were selected via RT‐qPCR and immunoblot assays (Figure S10B–D). The CmNAC‐NOR S,N / cr‐nor lines showed a typical phenotype associated with high levels of ethylene (Li et al, 2021; Jia et al, 2022), such as dwarfed plants with shorter internodes and more branches, while the CmNAC‐NOR A,S / cr‐nor lines showed no significant difference compared to the WT. Further, CmNAC‐NOR S,N overexpression fully rescued the unripening phenotype of the cr‐nor mutant, while CmNAC‐NOR A,S overexpression only partially rescued the unripening phenotype of the cr‐nor mutant (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Ethylene is an important regulator of fruit ripening, and ethylene biosynthesis, ethylene receptors, and ethylene response-related genes all affect fruit ripening ( Sunako et al, 1999 ; Varanasi et al, 2011 ; Tan et al, 2013 ). In apple, MdSnRK2-1 can phosphorylate MdHB1 and MdHB2 to enhance their protein stability and transcriptional activity toward MdACO1 , thereby promoting ethylene synthesis and fruit ripening ( Jia et al, 2022 ). Besides, the TF MdMYC2 is responsive to jasmonate treatment and directly binds to the promoters of MdACS1 , MdACO1 , and MdERF3 , thereby activating the ethylene signaling pathway during apple fruit ripening ( Li et al, 2017 ).…”
Section: Ripening and Storage Quality Of Apple Fruitmentioning
confidence: 99%